Cyborgs in Latin America - Brown, J.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2010)
A PDF version of this book is available for free in open access via the OAPEN Library platform, www.oapen.org . Cyborgs in Latin America explores the ways cultural expression in Latin America has grappled with the changing relationships between technology and human identity.
Keywords: Literature; Philosophy and social sciences; Ethnology; Culture; Ethnology -- Latin America; Social sciences -- Philosophy; Philosophy of mind; World Literature; Philosophy of the Social Sciences; Regional Cultural Studies; Latin American Culture; Social Theory; Philosophy of Mind